No shelf required : e-books in libraries - Polanka, Sue. (Chicago : American Library Association, 2011)
Sue Polanka brings together a variety of professionals to share their expertise about e-books with librarians and publishers. Providing forward-thinking ideas while remaining grounded in practical information that can be implemented in all kinds of libraries, the topics explored include an introduction to e-books and their different types, an overview of their history and development, e-book technology, why e-books are good for learning, and how librarians can market them to a wide range of users.--[back cover]
E-books on the Internet / James Galbraith -- Student learning and e-books / Jackie Collier and Susan Berg -- E-books in the school library / Shonda Brisco -- E-books in the public library / Amy Pawlowski ; case study by Blaise Dierks -- The academic library e-book / Lindsey Schell ; case study by Anne Behler -- Acquiring e-books / Carolyn Morris and Lisa Sibert -- The use and preservation of e-books / Alice Crosetto -- E-book standards / Emilie Delquiβe and Sue Polanka -- The future of academic book publishing : e-books and beyond / Rolf Janke.
Περιέχει βιβλιογραφια και ευρετήριο.
Keywords: Libraries and electronic publishing